2020
DOI: 10.1016/j.carbpol.2020.116342
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose nanofibrils prepared by twin-screw extrusion: Effect of the fiber pretreatment on the fibrillation efficiency

Abstract: Twin-screw extrusion (TSE) is a rather recent method to produce cellulose nanofibrils (CNFs) at a high solid content under continuous feeding. Here, never-dried commercial eucalyptus pulp was used as starting material to produce CNFs by TSE after a chemical pretreatment to introduce carboxylic groups via TEMPO-mediated oxidation and carboxymethylation. Five samples with acarboxyl content ranging from 800 to 1300 µmol.g-1 were produced to explore how the carboxyl content affects the aptitude of cellulose fibers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…The authors found that no significant fibrillation could be achieved when employing traditional NaOH-treated pulp fibers even after an oxidative pretreatment, a finding potentially attributable to the limited shearing capacity of the mini-TSE. To fibrillate commercially produced never-dried pulp, the authors explored more extensive TEMPO oxidation and carboxymethylation pretreatments . The pH level of TEMPO oxidation was deliberately raised to 10 to achieve a carboxyl content as high as 1350 μmol/g.…”
Section: Nonconventional Fibrillation Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The authors found that no significant fibrillation could be achieved when employing traditional NaOH-treated pulp fibers even after an oxidative pretreatment, a finding potentially attributable to the limited shearing capacity of the mini-TSE. To fibrillate commercially produced never-dried pulp, the authors explored more extensive TEMPO oxidation and carboxymethylation pretreatments . The pH level of TEMPO oxidation was deliberately raised to 10 to achieve a carboxyl content as high as 1350 μmol/g.…”
Section: Nonconventional Fibrillation Methodsmentioning
confidence: 99%
“…To fibrillate commercially produced never-dried pulp, the authors explored more extensive TEMPO oxidation and carboxymethylation pretreatments. 44 The pH level of TEMPO oxidation was deliberately raised to 10 to achieve a carboxyl content as high as 1350 μmol/g. By fibrillating pulp fibers modified with either TEMPO oxidation or carboxymethylation at a carboxyl content of 800 μmol/g, a 50 wt % fraction of nanoscale material was achieved.…”
Section: Nonconventional Fibrillation Methodsmentioning
confidence: 99%
See 3 more Smart Citations